Pedagogical Conditions of Moral and Economic Education of Children 6-7 Years Old in Play Activities - Khimmataliev, Dustnazar Omonovich; Burieva, Kibrio Ergashevna (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
Introducing a preschool-age child to real life and bringing him closer to it is one of the tasks of modern society. This is due to changes in the social life of all members of society (including preschool children), the importance of preparing a child for life, correctly orienting him in the ongoing phenomena of public life, as well as continuity between the first educational stages of the educational system - kindergarten and school. In this regard, one of the tasks of modern pedagogy of preschool childhood is to teach children the basics of economics. The problem of including economic education in the general education system has been considered by researchers recently. Along with such branches of education and upbringing as physical, labor, mental, aesthetic, economic, it acts as a relatively young one. The results of these studies are partial programs for the economic education of preschoolers, as well as educational and methodological manuals. At the same time, as the analysis of theoretical and methodological approaches to the problem of economic education of preschoolers has shown, its solution in the aspect of the moral development of children is not considered enough. The moral side plays a special role in economic education. The mere presence of knowledge and ideas about economics cannot mean that a child knows how to apply them correctly in life. Here, the other side immediately works - the moral side, which helps the child to understand the current situation. An urgent task of preschool pedagogy is to find effective ways to develop the personality of a preschooler, including his moral and economic education. It is generally recognized in Russian preschool pedagogy and psychology that the development of a child is carried out in the process of his active activity